The effects of dosage variation in black seed cumin oil (Nigella sativa L.) use on HbA1c levels and interleukin-17A expression in patients at risks of metabolic syndrome - Vitri Agustiarini; Endang Darmawan; Akrom Akrom (Universitas Ahmad Dahlan, 2019)
Metabolic syndrome causes an imbalance of the immune system and increased levels of HbA1c and IL-17A expression. Black cumin seed oil (BCSO) is known to have antioxidant and immunomodulatory properties. This study reports the effects of dosage variation in BCSO (1.5 and 3 ml per day for 20 days) on HbA1c levels and IL-17A expression in patients at risk of metabolic syndrome at Jetis 1 Public Health Center in Bantul, Yogyakarta. It employed a crossover design in which a total of 66 patients at risk of metabolic syndrome were divided into two groups receiving a sequence of different treatments. Group 1 (N=33) received treatment A first, which was BCSO at a dose of 1.5 ml/day for 20 days. Then, after a washout period of 7 days, it received treatment B, 3 ml of BCSO per day for 20 days. Group 2 followed the same procedure only vice versa, treatment B, then A. The HbA1c levels were measured by the mean plasma glucose (MPG) method, while the IL-17A expression was detected by flow cytometry. The average HbA1c level and IL-17A expression of the treatment groups were statistically analyzed with 95% confidence level. In response to the treatment regime, the HbA1c level of group 1 was 7.34 ± 2.51% (a decrease), and that of group 2 was 7.72 ± 2.44% (an increase). The IL-17 expression in group 1 was 3.74 ± 3.52% (a decrease), and the one in group 2 was 4.07 ± 3.65% (an increase). The effects of administering 1.5 ml and 3 ml BCSO per day for 20 consecutive days on Hb1c level (p=0.17) and IL-17A expression (p=0.67) were not significantly different. Most patients experience a decrease in HbA1c levels and IL-17A expression after the treatment. Insignificant differences between the two groups mean that at the doses of 1.5 ml/day and 3 ml/day for 20 days, BCSO exhibits the same effects in patients at risk of metabolic syndrome registered at Jetis 1 Public Health Center in Bantul, Yogyakarta.